Mercury occurrence modes in coal and the sulfur–mercury removal performance during coal pyrolysis. Issue 5 (23rd July 2019) - Zhang, Xiaoyang; Fu, Jiapeng; Dong, Yong; An, Donghai; Cui, Lin
Abstract: The mild pyrolysis of coal provided a promising alternative method for mercury and sulfur emission control before coal combustion. In the work, the occurrence modes of mercury in one lignite and two bituminous coals were characterized by temperature‐programmed decomposition with acid leaching. The removal performance of sulfur–mercury was also investigated by mild pyrolysis under weak oxidizing atmosphere. The results showed that the contents of organic‐bound mercury, pyrite‐bound mercury, and ash‐bound mercury were in the range of 35–55%, 15–45%, and 10–45%, with their release temperature in the range of 250–650, 500–700, and >700 °C, respectively. Sulfur and mercury were removed by fast pyrolysis at 500 °C under 2%O2 − N2 atmosphere, and the proportion of Hg 2+ in gas phase increased. The results indicated that the oxygen had participated in the decomposition of the mercury‐containing and sulfur‐containing compounds, and some stable mercury‐containing and sulfur‐containing compounds were easier for decomposition under weak oxidizing atmosphere at low temperature. The removal efficiency of sulfur and mercury significantly increased under weak oxidizing atmosphere by fast pyrolysis. It was because fast pyrolysis could accelerate the breakup of molecular bonds associated with sulfur–mercury at a low temperature. The pore structure of char produced by fast pyrolysis was improved, which was favorable for sulfur containing gas and mercury release.